2020
DOI: 10.4103/jhrs.jhrs_95_18
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Polycystic Ovary Syndrome: A Brief Systematic Review

Abstract: Background: Polycystic ovary syndrome (PCOS), the major endocrinopathy among reproductive-aged women, is not yet perceived as an important health problem in the world. It affects 4%–20% of women of reproductive age worldwide. The prevalence, diagnosis, etiology, management, clinical practices, psychological issues, and prevention are some of the most confusing aspects associated with PCOS. Aim: The exact prevalence figures regarding PCOS are limited and unclear. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(49 citation statements)
references
References 64 publications
3
46
0
Order By: Relevance
“…Women with polycystic ovary syndrome (PCOS) are an example of how something major can be missed without appropriate medical screening. The prevalence of PCOS is ~6–9% of adult women, and the condition can involve infrequent or prolonged menstrual cycles; but, some women with PCOS have regular monthly cycles [ 40 ]. These PCOS women, however, also typically have abnormal FSSH levels which affect their physiological responses to exercise.…”
Section: Factors Affecting Research Studiesmentioning
confidence: 99%
“…Women with polycystic ovary syndrome (PCOS) are an example of how something major can be missed without appropriate medical screening. The prevalence of PCOS is ~6–9% of adult women, and the condition can involve infrequent or prolonged menstrual cycles; but, some women with PCOS have regular monthly cycles [ 40 ]. These PCOS women, however, also typically have abnormal FSSH levels which affect their physiological responses to exercise.…”
Section: Factors Affecting Research Studiesmentioning
confidence: 99%
“…It seems that the criteria used for diagnosis can also impact the prevalence of infertility which is higher in women with polycystic ovary morphology in patients diagnosed according to Androgen Excess Society criteria (21,7%), while in patients diagnosed according to Rotterdam criteria infertility is present in only 6% of them [5].…”
Section: Fertility In Patients With Polycystic Ovary Syndromementioning
confidence: 99%
“…Moreover, it is a leading cause of female infertility [2,3] and the most common cause of anovulatory infertility [4]. A systematic review from 2020 [5] found that there is significant variation in prevalence probably according to ethnic background and design of the published studies, but also to diagnosis criteria used to identify the disease. Thus, they found that the reported prevalence of PCOS vary between 2,2% and 15-20%, with the studies using the Rotterdam criteria reporting the highest prevalence [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they are also at risk of developing psychological disturbances such as anxiety, depression, and eating disorders, which could be due to the physical manifestations of hyperandrogenism, such as hirsutism, male body configuration, and obesity [ 7 , 8 ]. The prevalence of PCOS varies, ranging from 4–20 percent depending on various subpopulations that are influenced by the environmental conditions and genetic variations [ 9 ]. Anovulation is one of the most significant reasons for infertility in females [ 10 ].…”
Section: Introductionmentioning
confidence: 99%